Foreign assistance or attack? Impact of the expanded Global Gag Rule on sexual and reproductive health and rights in Kenya. Issue 3 (17th December 2020) - Ushie, Boniface Ayanbekongshie; Juma, Kenneth; Kimemia, Grace; Magee, Maggie; Maistrellis, Emily; McGovern, Terry; Casey, Sara E.
Abstract: In 2017, the Trump Administration reinstated and expanded the Global Gag Rule (GGR). This policy requires non-governmental organisations (NGOs) not based in the US to certify that they will not provide, counsel, refer, or advocate for abortion as a method of family planning in order to receive most categories of US global health assistance. Robust empirical evidence demonstrating the policy's impacts is acutely lacking. This paper describes the effects of the expanded GGR policy in Kenya eighteen months after its reinstatement. We conducted semi-structured interviews with purposively selected representatives of US- and non-US-based NGOs, as well as managers and health providers at public and private health facilities, between September 2018 and March 2019. Organisations reported critical funding loss as they were forced to choose between US government-funded projects and projects supporting safe abortion. This resulted in the fragmentation of sexual and reproductive health and HIV services, and closure of some service delivery programmes. At public and private health facilities, participants reported staffing shortages and increased stock-outs of family planning and safe abortion commodities. The expanded GGR's effects transcended abortion care by also disrupting collaboration and health promotion activities, strengthening opposition to sexual and reproductive health and rights in some segments of Kenyan civil society and government. Our findings indicate that the GGR exposes and exacerbates the weaknesses and vulnerabilities of the Kenyan health system, and illuminates the need for action to mitigate these harms.